Digital Privacy and Human Rights : The Legal Challenges of Mass Surveillance - Miguel Torres; Sofia Beatriz Mendoza (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The rise of mass surveillance technologies has raised significant concerns regarding digital privacy and human rights. This paper explores the legal implications of government surveillance programs and their impact on fundamental rights, such as freedom of expression and the right to privacy. Through a comparative analysis of data protection laws in different jurisdictions, this study assesses the balance between national security and individual rights in the digital age.